DESIGN AND REALIZATION OF DUAL BAND MICROSTRIP SIW ANTENNA - Belen, Aysu; Gunes, Filiz (YILDIZ TECHNICAL UNIV, 2020)
Herein, realization of a high performance dual band microstrip antenna via the use of Substrate Integrated Waveguide technology (SIW) has been studied. Firstly, a 3D Electromagnetic based SIW antenna design has been modeled in CST Microwave Studio. The proposed dual band antenna is aimed to operate at 10 & 24 GHz frequency. After obtaining an optimal simulated model, the proposed antenna is fabricated on Rogers's 4350 high performance substrate. The simulation and measurement results of the proposed SIW antenna are compared. As it can be seen from the measurement results the proposed antenna achieves a measured gain characteristic of 6 and 7.2 dB at 10 & 22 GHz frequency with a S-11 level of less than -10 dB.
Keywords: Microstrip antenna; X band; K band; substrate integrated wavequide; SIW; radar; SLOT ANTENNA; IMPEDANCE; SQUARE; Engineering